Pelvic Incidence Affects Age-adjusted Alignment Outcomes in a Population of Adult Spinal Deformity. Issue 1 (February 2021) - Passias, Peter G.; Bortz, Cole A.; Segreto, Frank A.; Horn, Samantha R.; Pierce, Katherine E.; Manning, Jordan; Vasquez-Montes, Dennis; Diebo, Bassel; Lafage, Renaud; Lafage, Virginie
Abstract : Study Design: A single-center retrospective cohort study. Objective: The objective of this study was to assess the effects of patient height and pelvic incidence (PI) on age-adjusted alignment outcomes of surgical adult spinal deformity (ASD) patients. Summary of Background Data: Patient height and PI have yet to be evaluated for their individual effects on achieving age-adjusted alignment targets. Methods: Surgical ASD patients were grouped by percentile (low: <25th; normative: 25th–75th; high: >75th) for height and PI. Correction groups were generated at postoperative follow-up for actual alignment compared with age-adjusted ideal values for pelvic tilt (PT), pelvic incidence minus lumbar lordosis mismatch (PI−LL), and sagittal vertical axis, and PI-adjusted ideal alignment values for sacral slope (SS), as derived from clinically relevant formulas. Means comparison tests assessed differences in rates of matching ideal alignment (±10 y threshold for age-adjusted targets; −7 to 5 degrees measured minus ideal for SS) across height and PI groups. Results: Breakdown of all included 198 patients by PI group: low (25%, 38±11 degrees), normative (50%, 57±5 degrees), high (25%, 75±7 degrees). Breakdown of patient height groups: low (25%, 1.52±0.04 m), normative (50% 1.64±0.05 m), and high (25%, 1.79±0.06 m). Overall, 29% of patients met postoperative age-adjusted alignment targets for PT, 23% for PI−LL, and 25% for sagittal vertical axis. Overall, 26% of patients met PI-adjusted SS alignment. There were no differences across patient height groups in rates of achieving adjusted alignment target (all P >0.05). Patients with high PI reached age-adjusted ideal alignment for PT at a lower rate (16%) than patients with normative (33%) or low PI (33%, P =0.056). Of patients that matched at least 1 ideal alignment target, those with high PI showed inferior preoperative to postoperative changes in EuroQol 5-dimension questionnaire as compared with normative and low PI patients ( P =0.015). Conclusions: Patients with high PI reached ideal postoperative age-adjusted PT alignment at a lower rate than patients with normative and low PI. Height had no impact on postoperative age-adjusted alignment outcomes. Current postoperative ideal alignment targets may warrant an adjustment to account for PI.